Relationship between the extent of coronary artery disease and in-stent restenosis in patients with acute ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention - Erkan Yıldırım; Murat Çelik; Uygar Çağdaş Yüksel; Barış Buğan; Yalçın Gökoğlan; Suat Görmel; Salim Yaşar; Mustafa Koklu; Atila İyisoy; Cem Barçın (KARE Publishing, 2017)
Objective: The pathophysiological mechanism of in-stent restenosis (ISR) is different from atherosclerosis of native coronary arteries. The aim of this study was to evaluate the relationship between ISR and the extent of coronary artery disease (CAD), and to identify other risk factors associated with ISR in ST-segment elevation myocardial infarction (STEMI) patients. Methods: A total of 372 consecutive patients presenting with first acute STEMI who were successfully treated with primary percutaneous coronary intervention within 12 hours from the onset of symptoms and who had an angiographic follow-up at 3 months were included in the study. The extent of CAD was calculated using the Gensini score. Results: The incidence of ISR observed in our group of patients was 23.4% (n=87). The mean Gensini score was significantly higher in patients with ISR when compared with group without restenosis (69 [range: 51-90] vs 42 [range: 32-61]; p<0.001). The presence of diabetes mellitus, left ventricular ejection fraction (LVEF), and low-density lipoprotein cholesterol (LDL-C) level differed significantly between the 2 groups (p<0.05 for all). Stent diameter and stent length were found to be significantly different between the ISR group and the no-restenosis group (p<0.05 for both). In multivariate logistic regression analysis, the Gensini score, stent diameter, stent length, LVEF, and LDL-C were independently associated with ISR. Conclusion: Despite the differences in the underlying pathophysiological mechanism of ISR and native coronary atherosclerosis, patients with a greater extent of CAD should be considered candidates for future stent restenosis.